Cation‐Selective Channel Regulated by Anions According to Their Hofmeister Ranking. Issue 13 (15th February 2017) - Gurnev, Philip A.; Roark, Torri C.; Petrache, Horia I.; Sodt, Alexander J.; Bezrukov, Sergey M.
Abstract: Specificity of small ions, the Hofmeister ranking, is long‐known and has many applications including medicine. Yet it evades consistent theoretical description. Here we study the effect of Hofmeister anions on gramicidin A channels in lipid membranes. Counterintuitively, we find that conductance of this perfectly cation‐selective channel increases about two‐fold in the H2 PO4 − 3 − 4 − <SCN − series. Channel dissociation kinetics show even stronger dependence, with the dwell time increasing about 20‐fold. While the conductance can be quantitatively explained by the changes in membrane surface potential due to exclusion of kosmotropes from (or accumulation of chaotropes at) the surface, the kinetics proved to be more difficult to treat. We estimate the effects of changes in the energetics at the bilayer surfaces on the channel dwell time, concluding that the change would have to be greater than typically observed for the Hofmeister effect outside the context of the lipid bilayer. Abstract : Hofmeister effects : The conductance of a purely cation‐selective peptide pore is regulated by anions in correlation with their position in the Hofmeister series (see picture). Moreover, the pore conformational dynamics are highly sensitive to the anion species. Both effects are related to preferential depletion of kosmotropic anions (accumulation of chaotropic anions) at the membrane–water interface.